2017
DOI: 10.1007/s10725-017-0350-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the BZR transcription factor family and its expression in response to abiotic stresses in Zea mays L.

Abstract: Brassinosteroids (BRs) are plant specific steroidal hormones that play diverse roles in regulating a broad spectrum of plant growth and developmental processes, as well as, in responding to various biotic and abiotic stresses. Extensive research over the years has established stress-impact-mitigating role of BRs and associated compounds in different plants exposed to various abiotic and biotic stresses, suggesting the idea that they may act as immunomodulators, thus opening new approaches for plant resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 50 publications
7
35
0
Order By: Relevance
“…In our study, six, eight, eight, twelve and thirteen BZR-coding protein sequences were identified in F.vesca , P. mume , P. persica , P. communis and P. bretschneideri , respectively ( Table S1 ). Compared with other gene families in the studied species, the BZR gene family is of relatively small size, which is consistent with the previous studies such as six, six, eleven and fifteen BZR genes in A. thaliana , E. grandis , Z. mays and B. rapa , respectively ( Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). Interestingly, the numbers of BZR genes have a certain degree of expansion in both P. communis and P. bretschneideri , when compared with those in F. vesca , P. mume and P. persica .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, six, eight, eight, twelve and thirteen BZR-coding protein sequences were identified in F.vesca , P. mume , P. persica , P. communis and P. bretschneideri , respectively ( Table S1 ). Compared with other gene families in the studied species, the BZR gene family is of relatively small size, which is consistent with the previous studies such as six, six, eleven and fifteen BZR genes in A. thaliana , E. grandis , Z. mays and B. rapa , respectively ( Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). Interestingly, the numbers of BZR genes have a certain degree of expansion in both P. communis and P. bretschneideri , when compared with those in F. vesca , P. mume and P. persica .…”
Section: Resultssupporting
confidence: 91%
“…As previously reported, the members of the BZR gene family were found to be involved in the regulation of various processes in plants, and the positive roles of the BZR genes in BR signal transduction have been well studied in plants, such as A. thaliana , Brassica rapa , Eucalyptus grandis and Zea mays ( Clouse et al, 1996 ; Li and Chory, 1997 ; Ye et al, 2010 ; Clouse, 2011 ; Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). However, no systematic, in-depth study of the BZR gene family has been reported in five Rosaceae species, including F. vesca , P. mume , P. persica , P. communis , and P. bretschneideri .…”
Section: Resultsmentioning
confidence: 79%
“…Expression of the other six genes was ubiquitous. Moreover, the ZmBZR1 genes showed differential expression pattern in response to abiotic stresses and light signal [93,94].…”
Section: Regulation Of the Br-dependent Gene Expression In Monocotsmentioning
confidence: 99%
“…As some of the most important crops worldwide for both humans and domestic animals, further efforts should be made for mining and characterizing genes related to legume growth, development, and stress responses ( Dixon and Sumner, 2003 ; Graham and Vance, 2003 ). The BZR genes encode important TFs that function in the regulation of plant growth and development and the BZR-mediated abiotic stress response and have been identified and characterized in detail in only a few plant species, including A. thaliana , Brassica rapa , and Zea mays ( Yin et al, 2005 ; Saha et al, 2015 ; Manoli et al, 2018 ). Some predictions in public databases (such as iTAK and PlantTFDB) resulting from genome-scale automatic annotation pipelines have resulted in identification of new BZR genes ( Zheng et al, 2016 ; Jin et al, 2017 ); however, the genome-wide identification, characterization, and expression profile analysis of BZR gene evolution and function in legumes has yet to be completed.…”
Section: Introductionmentioning
confidence: 99%